On The Impact of User Payload on Deployment Requirements of LTE Networks - A., Hameed; Oudah, Ali A. (WSEAS, 2014)
Ever since its inception, Long Term Evolution (LTE) of Universal Mobile Telecommunications System (UMTS) standard has gained great deal of momentum from wireless operators as well as end users. This paper addresses the impact of user or traffic load in LTE cells on total harmful interference emitted towards a victim cell. This is done through deriving coexistence requirements, in terms of land separation, when deploying LTE base stations in band 2.6 GHz. In view of the developed model and results, the interference radiated from the aggressor to the victim is directly proportional with the aggressor’s traffic load. In other words, the higher the payload of the aggressor, the higher the interference received by the victim.